Hemodialysis Therapy Compliance in Chronic Kidney Disease Patients - Yoppy Indra Wahyudi; Lisna Anisa Fitriana; Tita Puspita Ningrum; Natasya Natasya (Indonesian Journal of Community Development, 2023)
Background: Chronic kidney disease (CKD) is a progressive and irreversible impairment or decrease in kidney function, occurring gradually over three months or more as a result of permanent damage to the kidney structure. One of the management for patients with CKD is hemodialysis therapy which replaces kidney function to eliminate the remnants of protein metabolism products and remove excess fluid and electrolytes through hemodialysis machines, and artificial kidneys (dialyzer). One of the major problems that contribute to failure in the management of hemodialysis therapy is patient compliance. Objective: This study was conducted to identify adherence to hemodialysis therapy in CKD patients in Bandung City Hospital. Methods: research design using descriptive analysis on 44 respondents with purposive sampling technique. Data collection using the End Stage Renal Disease–Adherence Questionnaire (ESRD-AQ) questionnaire. Univariate data analysis using frequency distribution. Results: In CKD patients undergoing hemodialysis therapy at the Bandung City Hospital as many as 33 respondents (75%) were compliant and 11 people (25%) were not compliant in undergoing hemodialysis therapy. The domains of adherence of CKD patients who were most adhered to by respondents were therapy attendance (75%), shortening duration (79.55%), length of time shortening therapy (79.55%), and medication adherence (52.27%). Conclusion: most of the patients were obedient in undergoing hemodialysis therapy. The suggestion from this study is that the hospital should include an assessment of the level of compliance of patients undergoing hemodialysis therapy as an additional domain in indicators of the quality of health services in the hemodialysis room of the Bandung City Hospital.